Paired electrocatalysis in 5-hydroxymethylfurfural valorization - Qu, Dalong; He, Shuijian; Chen, Lianhua; Ye, Yifan; Ge, Qingmei; Cong, Hang; Jiang, Nan; Ha, Yang (Frontiers in Chemistry, 2022)
5-Hydroxymethylfurfural (HMF) has aroused considerable interest over the past years as an important biomass-derived platform molecule, yielding various value-added products. The conventional HMF conversion requires noble metal catalysts and harsh operating conditions. On the other hand, the electrocatalytic conversion of HMF has been considered as an environmentally benign alternative. However, its practical application is limited by low overall energy efficiency and incomplete conversion. Paired electrolysis and highly efficient electrocatalysts are two viable strategies to address these limitations. Herein, an overview of coupled electrocatalytic HMF hydrogenation or hydrogen evolution reaction (HER) with HMF oxidation as well as the associated electrocatalysts are reviewed and discussed. In this mini-review, a brief introduction of electrocatalytic HMF upgrading is given, followed by the recent advances and challenges of paired electrolysis with an emphasis on the integration HMF electrohydrogenation with HMF electrooxidation. Finally, a perspective for a future sustainable biomass upgrading community based on electrocatalysis is proposed.